You may want to review multiplying terms with roots and quadratic equations first.

To solve equations involving radicals, you want to get the term
with the radical in it by itself on one side. For example, if you
have to solve 3√(*x* − 1) − 1 =
−*x*, you add 1 to both sides to get 3√(*x*
− 1) = −*x* + 1. Next, you square both sides. The
square of the left-hand side is 9(*x* − 1) (remember
the definition of square roots), and the square of the right-hand
side is *x*^{2} − 2*x* + 1, so the new
equation is 9(*x* − 1) = *x*^{2} −
2*x* + 1. This is just a quadratic equation that we need to
solve. (Sometimes we're lucky and it's linear instead.) Getting
everything on one side gives us *x*^{2} −
11*x* + 10 = 0. This has two solutions: *x* = 1
or *x* = 10.

We're not quite done. The problem is that squaring both sides of
an equation can add solutions that weren't there before. So
it's *essential* that you check these solutions in the
original equation. (Of course, checking is a good idea even with
simpler equations; but here it's necessary.) When we do that, we
find that *x* = 1 checks out (both sides come out to
−1) but *x* = 10 doesn't (the left-hand side comes out
to 8, the right-hand side to −10). So *x* = 1 is the
only solution.